Mid-term impact of home-based follow-up care on health-related quality of life of hypertensive patients at a teaching hospital in Ilorin, Nigeria - Bolarinwa, Oladimeji Akeem; Juni, Muhamad Hanafiah; Mohd Zulkefli, Nor Afiah; Md Said, Salmiah; Akande, Tanimola Makanjuola (Medknow Publications, 2019)
Background: Health-related quality of life (HRQoL) is an important clinical outcome assessment in hypertension management, given the lifelong (chronicity) nature and the need for daily self-management for hypertensive patents. Of some of the studies that implemented home-based interventions on hypertension globally, the HRQoL is rarely used as a primary outcome measure. This study developed, implemented, and assessed the impact of home-based follow-up care (HBFC) on HRQoL of hypertensive patients attending outpatients' clinics in Ilorin, Nigeria. Materials and methods: A total of 149 and 150 patients were randomized to intervention and usual care (control) groups, respectively. A 12-month task-shifting (nurse-driven) HBFC intervention was administered to intervention group. The mid-term impact of intervention on HRQoL was assessed after 6 months intervention. Data were analyzed with intention-to-treat principle. Treatment effects were measured with the t-tests, analysis of covariance, and multivariate analysis of covariance analysis. Significant levels were set at P < 0.05 and 95% confidence interval. Results: The between-group treatment effect was not statistically significant (P > 0.05), whereas the within-group treatment effects were statistically significant for both the intervention and control arms (P < 0.05) at 6 months. After controlling for age and baseline HRQoL, the intervention group had an improved physical component of HRQoL than the control group. The intervention group also had statistically significant improvement in blood pressure control, medication adherence, and symptom counts (P < 0.05). Conclusion: The HBFC intervention for hypertensive patients impacted positively on physical component of HRQoL after controlling for baseline HRQoL and age of the patients at 6 months post-intervention.